PERKEMBANGAN TEKNOLOGI PANGAN DALAM PEMENUHAN KEBUTUHAN GIZI MASYARAKAT - Is Zunaini Nursinah (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2003)
One of the human basic needs is food whose supply depends on the development of agricultural technology, food is a product resulted from agriculture in urban area whose product is used to meet the need of families. Food supply is influenced by increasing population, extintion of environtment order, insufficient supply and misditribution, poverty as well as insufficient job vacancies, underdevelopment undereducation, govemtment politics, insufficient knowledge of nutrient fron society, and anti nutrient compound and toxin in food. Fermend food comes from food technology in the field of biotechnology. Availability of food should also fulfil nutrient neened from each level measured by Minimum Daily Requirement (MDR) and calculated by Recommended Daily Acquired (RDA). The neded of nutrien from society can be measured by direct and indirect methods.